2004
DOI: 10.1023/b:biry.0000029847.40511.26
|View full text |Cite
|
Sign up to set email alerts
|

Structural Investigations and Identification of the Extracellular Bacteriolytic Endopeptidase L1 from Lysobacter sp. XL1

Abstract: The N-terminal amino acid sequence (23 amino acid residues) and the amino acid composition of the extracellular bacteriolytic enzyme L1 of 21 kD from the bacterium Lysobacter sp. XL1 have been determined. The enzyme was hydrolyzed by trypsin, the resulting peptides were isolated, and their primary structures were determined. A high extent of homology (92%) of the N-terminal amino acid sequence and the primary structure of isolated peptides of the enzyme L1 (62 amino acid residues or 31% of protein sequence) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The most investigated among these enzymes are lytic proteases L1 and L5. The gene structures of these proteins ( alp A and alp B) suggest them to be synthesized as pre-pro-proteins, as has been shown for the alpha-lytic protease of Lysobacter enzymogenes , which is homologous to them [Granovsky et al, 2010[Granovsky et al, , 2011Lapteva et al, 2012;Muranova et al, 2004]. In accordance with this, it could be assumed that secretion of enzymes L1 and L5 from the cytosol into the environment should proceed by the same protocol, in two stages.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The most investigated among these enzymes are lytic proteases L1 and L5. The gene structures of these proteins ( alp A and alp B) suggest them to be synthesized as pre-pro-proteins, as has been shown for the alpha-lytic protease of Lysobacter enzymogenes , which is homologous to them [Granovsky et al, 2010[Granovsky et al, , 2011Lapteva et al, 2012;Muranova et al, 2004]. In accordance with this, it could be assumed that secretion of enzymes L1 and L5 from the cytosol into the environment should proceed by the same protocol, in two stages.…”
Section: Introductionmentioning
confidence: 95%
“…Enzymes L1 and L5 are synthesized in the bacterial cytosol as pre-pro-proteins, which suggests secretion through the cytoplasmic membrane via a Sec-export mechanism [Granovsky et al, 2010[Granovsky et al, , 2011Muranova et al, 2004;Lapteva et al, 2012]. For Lysobacter , there has been no data defining the existence of a similar mechanism.…”
Section: Formation Of Vesicles In Lysobacter Sp and Their Role In Sementioning
confidence: 99%
“…The enzyme L5 is homologous to endopeptidase L1 of Lysobacter sp. XL1 and α-lytic protease of Lysobacter enzymogenes [Muranova et al, 2004], both known to digest the Gly-Gly and mur-D -Ala bonds in the peptidoglycan of S. aureus . Therefore, we have investigated the action of enzyme L5 on the peptidoglycan of S. aureus 209Р with and without teichoic acids.…”
Section: Action Of Enzyme L5 On Bacterial Cell Wall Componentsmentioning
confidence: 99%
“…Earlier, four lytic enzymes L1-L4 were isolated from the culture liquid of Lysobacter sp. XL1 and characterized [Muranova et al, 2004;Stepnaya et al, 1992Stepnaya et al, , 1996aStepnaya et al, , b, 2005]. An additional protein fraction possessing lytic activity against the autoclaved cells of Staphylococcus aureus 209P was found during optimization of the scheme of lytic enzymes purification.…”
Section: Introductionmentioning
confidence: 99%
“…AlpA and AlpB are homologous proteins that are close in size, and their pre-pro-protein sequences are 62% identical [Granovsky et al, 2010[Granovsky et al, , 2011. These enzymes also exhibit a homology with the well-investigated α-lytic protease from L. enzymogenes [Epstein and Wensink, 1988;Muranova et al, 2004], for which its pro part has been found to be involved in its folding and to be autocatalytically split off after the enzyme takes a native conformation [Fujishige et al, 1992;Silen et al, 1989].…”
mentioning
confidence: 99%